1980
DOI: 10.1161/01.hyp.2.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of dietary sodium in man: a preliminary report.

Abstract: SUMMARY The effect of dietary sodium manipulation was studied In 27 normal subjects and 19 patients with borderline hypertension. Sodium-loading caused an Increase in blood pressure (BP) in 14 of 19 borderline hypertensive patients but in only 4 of 27 normal subjects (X* = 13.85, p < 0.01). In the normal subjects, a 10 mEq sodium diet resulted in a fall in supine mean blood pressure (MBP) of 43% after 4 days (p < 0.05). Cardiac index (CI) measured by echocardiography fell by 4.0%, while total peripheral resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(32 citation statements)
references
References 22 publications
3
28
0
1
Order By: Relevance
“…4 " 13 In the present study, we found the prevalence of sodium sensitivity to be approximately 16% in normotensive subjects and 29% in subjects with borderline hypertension. Subsequently, Weinberger et al 8 and Luft and Weinberger 10 noted that the prevalence of sodium sensitivity was higher in hypertensive than in normotensive groups.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…4 " 13 In the present study, we found the prevalence of sodium sensitivity to be approximately 16% in normotensive subjects and 29% in subjects with borderline hypertension. Subsequently, Weinberger et al 8 and Luft and Weinberger 10 noted that the prevalence of sodium sensitivity was higher in hypertensive than in normotensive groups.…”
Section: Discussionsupporting
confidence: 53%
“…4 ' 13 -"• 18 Stroke volume was determined by subtracting the systolic from diastolic volumes. Cardiac output was calculated as the product of simultaneous heart rate and stroke volume averaged over 10 seconds.…”
Section: Echocardiographic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26] In addition, our results show that in hypertensives, changes in plasma sodium are related directly to the response of the renin-angiotensin system, which suggests that changes in plasma sodium per se could be a drive that changes plasma renin activity, 27 aldosterone, and atrial natriuretic peptide release that occur with changes in salt intake.…”
Section: Discussionmentioning
confidence: 87%
“…There are also different classifications of salt sensitivity. Some investigators consider it necessary to have a mean BP increase of 5% (12), others of 10% (13) from LSD to HSD to classify someone as being salt sensitive. Other investigators prefer to consider absolute values, for example, a mean BP increase of 3 mmHg between diets (14).…”
mentioning
confidence: 99%